Already out. Notes on the relationship between function and nature of the sentence, process and public opinion (Società e diritti, 2018)
Crime rate is decreasing in Italy, predatory and street crimes in particular. The repressive apparatus however is progressively made worse, theft and rape cases can be taken as an example. This is the method used to face the widespread perception of rising insecurity. Security is conceived as a result of the rules and their effectiveness. Something to get a hold of through law. Especially by using criminal enforcement means which are assimilated tout court to imprisonment. Consequence are the increase of penitentiary institutions, the immediate incarceration of alleged offenders, alongside with the denial of any benefit that could possibly shorten the duration of imprisonment. We are witnessing the identification between what is considered crimeand what generates social alarm, the bond between process and sanction is neglected and the conception of security is stated beginning from the physical control of individuals. The matter of fundamental rights is colonized by the security reason.Key words: Security, fundamental rightsCriminal enforcement